Diplomasi Vaksin Dalam Kerja Sama Indonesia Dengan Tiongkok Di Masa Pandemi Covid-19 - Yahya, Jihan Nadya; Simatupang, Helga Yohana (Universitas Cenderawasih, 2023)
The Covid-19 pandemic has disrupted all aspects of our life. It forced us to adopt to a new normal situation and take innovative measures in tackling the pandemic in order to survive. Health experts developed vaccines to reduce human death and helped people recover from the virus infection. The development of the vaccines has made a great contribution to global health. Indonesia itself used seven vaccine variants, which have been approved by the government for nationwide use. Among them are sinovac and sinopharm vaccines, which were made by China. China has helped Indonesia in many ways, in the provision of vaccines, and the bilateral relations between Indonesia and China continued to increase. This article shows that the provision of Covid-19 vaccines contributed to the strong relations between Indonesia and China, and this was channelled through what was called vaccine diplomacy. In this article, the author will be using the global politics theory to analyze the issue. Through this article, scholars can identify the challenges and benefits of the cooperation. KEYWORDS China; Cooperation; Diplomacy; Indonesia; Vaccine